2004
DOI: 10.1021/nl049029h
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Voltage Controlled Enzymatic Nanoreactor Produced in the Tip of a Nanopipet

Abstract: We report the enzymatic cleavage of fluorescein diphosphate (FDP) by alkaline phosphatase (AP) confined in the tip of a nanopipet with a volume of approximately 100 attoliters. The amount of enzyme that reversibly adsorbs in the pipet tip was shown to be proportional to the enzyme concentration in the bath. Increasing the voltage applied to the pipet, up to 1.5 V, linearly controls the substrate turnover rate by increasing the flow of substrate out of the pipet. This work opens up possibilities of highly minia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…The nanopipets used in this work can be integrated with ion conductance microscopy to scan (t À < dT) the surface of living cells and perform targeted delivery on demand (t À > dT) in a cell area of choice. Another exciting application is the possibility of using the region inside the nanopipet, near the tip as an ultrasmall reaction volume, 39 where small molecular populations are pulsed back and forth and interact with each other, with the reaction products simultaneously delivered and detected by the nanopore.…”
Section: Resultsmentioning
confidence: 99%
“…The nanopipets used in this work can be integrated with ion conductance microscopy to scan (t À < dT) the surface of living cells and perform targeted delivery on demand (t À > dT) in a cell area of choice. Another exciting application is the possibility of using the region inside the nanopipet, near the tip as an ultrasmall reaction volume, 39 where small molecular populations are pulsed back and forth and interact with each other, with the reaction products simultaneously delivered and detected by the nanopore.…”
Section: Resultsmentioning
confidence: 99%
“…Depending on parameters such as glass thickness, temperature, and pulling force, diameters down to nanometer range can be achieved. 12,13 First experiments have shown that nanocapillaries allow for the detection of DNAcoated colloids. 14 Our recent work revealed that it is possible to differentiate not only colloids of different size but also DNA-coated colloids from uncoated colloids.…”
mentioning
confidence: 99%
“…Nanopipettes are versatile enough to be used as a tool for sensitive detection in biomedical applications. Optical detection of fluorescently labeled macromolecules such as DNA or proteins with nanopipettes has been reported. , Fully electrical detection has also been shown with similarly sized nanoparticles, whose flow through the nanopipette opening creates temporal current blockades . The ultimate goal of these efforts, the label-free real-time electrical detection of single molecules, could be achieved eventually by a deeper understanding of the fundamental characteristics of nanopipette electrodes under an external electric field.…”
mentioning
confidence: 99%